Fatigue Performance of AISI 4340 Steel Ni-Cr-B-Si-Fe HVOF Thermal Spray Coated - Vieira, L. F S; Voorwald, H. J C [UNESP]; Cioffi, M. O H [UNESP] (Elsevier, 2015)
Coatings are deposited on high strength materials to improve the surface degradation resistance of several elements. As a consequence, the fatigue strength of coated materials is significantly influenced by internal residual stresses. Despite the fact that hard chromium electroplated is used to guarantee combinations of adhesion, hardness, corrosion and wear resistance, the method decreases the fatigue resistance of aeronautical components due to the high tensile residual stresses and microcracks density contained in the coating. In order to avoid this problem thermally sprayed HVOF coatings and shot peening process are widely used to improve surface properties of several alloys. The aim of the present study is to analyze the influence of Ni-Cr-B-Si-Fe coating applied by HVOF process on the axial fatigue strength of AISI 4340 steel. The shot peening effect on the fatigue results of coated AISI 4340 steel was also evaluated. The fractured fatigue specimens were investigated using a scanning electron microscope in order to obtain information about the crack initiation points.
Keywords: AISI 4340 steel; fatigue; residual stresses; shot peening; Thermal spray coating